RANCANG BANGUN SISTEM ANTARMUKA KOMPUTER UNTUK PENGHITUNGAN LAJU ALIRAN KALOR KONDUKSI PADA MATERIAL PADAT MENGGUNAKAN PROTOKOL RS485 - Nailatul Ilmi; Suryono Suryono (Youngster Physics Journal, 2012)
This research is about computer interface system for determining conduction heat flow rate on massive material using RS485 protocol. The system can be used for monitoring equipment in an industrial feasibility by measuring the rate of heat flow simultaneously at some measuring points of each measurement point that consists of some channels.Heat flow rate monitoring system uses temperature sensor LM35. This sensor serves to convert the temperature into a voltage whose  the results converted into digital signals by the ADC0 and ADC1 microcontroller which then signals are transmitted to the computer using the RS485 protocol.This system has been realized and can display the measured temperature at two different measurement points with two input channels and this system can also calculate the heat flow rate of each its points. The obtained results can be displayed graphically and also can be stored in Microsoft Excel. Keyword : heat flow rate, RS485 protocol, monitoring system, temperature sensor LM35